Did I find the right examples for you? yes no

All Samples(6)  |  Call(6)  |  Derive(0)  |  Import(0)
```Add one Hermite series to another.

Returns the sum of two Hermite series `c1` + `c2`.  The arguments
are sequences of coefficients ordered from lowest order term to
highest, i.e., [1,2,3] represents the series ``P_0 + 2*P_1 + 3*P_2``.

Parameters
----------
c1, c2 : array_like
1-D arrays of Hermite series coefficients ordered from low to(more...)
```

```        def hermeadd(c1, c2):
"""
Add one Hermite series to another.

Returns the sum of two Hermite series `c1` + `c2`.  The arguments
are sequences of coefficients ordered from lowest order term to
highest, i.e., [1,2,3] represents the series ``P_0 + 2*P_1 + 3*P_2``.

Parameters
----------
c1, c2 : array_like
1-D arrays of Hermite series coefficients ordered from low to
high.

Returns
-------
out : ndarray
Array representing the Hermite series of their sum.

--------
hermesub, hermemul, hermediv, hermepow

Notes
-----
Unlike multiplication, division, etc., the sum of two Hermite series
is a Hermite series (without having to "reproject" the result onto
the basis set) so addition, just like that of "standard" polynomials,
is simply "component-wise."

Examples
--------
>>> hermeadd([1, 2, 3], [1, 2, 3, 4])
array([ 2.,  4.,  6.,  4.])

"""
# c1, c2 are trimmed copies
[c1, c2] = pu.as_series([c1, c2])
if len(c1) > len(c2) :
c1[:c2.size] += c2
ret = c1
else :
c2[:c1.size] += c1
ret = c2
return pu.trimseq(ret)
```

```                tgt[i] += 1
tgt[j] += 1
res = herme.hermeadd([0]*i + [1], [0]*j + [1])
assert_equal(trim(res), trim(tgt), err_msg=msg)

```
```                ci = [0]*i + [1]
cj = [0]*j + [1]
quo, rem = herme.hermediv(tgt, ci)
```

```                tgt[i] += 1
tgt[j] += 1
res = herme.hermeadd([0]*i + [1], [0]*j + [1])
assert_equal(trim(res), trim(tgt), err_msg=msg)

```
```                ci = [0]*i + [1]
cj = [0]*j + [1]
quo, rem = herme.hermediv(tgt, ci)